THE EVALUATION OF MASTER OF EDUCTION PROGRAM IN EDUCATIONAL ADMINISTRATION FACULTY OF EDUCATION, RAJABHAT RAJANAGARINDRA UNIVERSITY (REVISED CURRICULUM 2021) - Sinlapaprasert, Sarunyaporn; Hunsaen, Sansern; Aiemphaya, Kanporn; Kaewmamuang, Patcharin; Boonprasert, Amnat (Journal of MCU Nakhondhat, 2023)
This research article aimed to 1) Study the aspect of curriculum context 2) Study the aspect of initial factors 3) Study the aspect of process according to the opinion of full - time instructors, lecturers, students, and 4) Assess desirable characteristics of students according to the opinion of student’s users. Sample group consisted of 6 full time instructors, 5 lecturers, 44 students, 52 employers, a total of 107 participants. The method was Evaluation Research in zip format based on Stufflebeam concept. Data was analyzed by Frequency, Percentage, Mean, Standard Deviation, and Content Analysis. The result showed curriculum assessment was appropriate as follows 1) According to full - time instructors, the overall and each aspect at the highest level was the aspect of initial factors: study plan ( = 4.94, S.D. = 0.14) The second highest was qualification of students ( = 4.92, S.D. = 0.20) The last aspect was the process: instructor management and development ( = 4.67, S.D. = 0.58) 2) According to lecturers, the overall and each aspect at the highest level was the aspect of initial factors: study plan ( = 4.93 , S.D. = 0.15) The second highest was the aspect of process: curriculum management ( = 4.89, S.D. = 0.19) The last aspect was curriculum context: curriculum objectives ( = 4.72, S.D. = 0.54) 3) According to students, the overall and each aspect at high level was the aspect of process : instruction setting and evaluation ( = 4.57, S.D. = 0.65) The second high was the aspect of process: student satisfaction and complaint management ( = 4.52, S.D. = 0.61) The last aspect was process: resource ( = 4.19, S.D. = 0.76) and the assessment of student’s desirable 4) According to student’s users, the quality of students was overall at high level in the aspect of skill for interpersonal relationship and responsibility ( = 4.63, S.D. = 0.60) the second high was moral and ethics ( = 4.55, S.D. = 0.61) and the last aspect was aspect of knowledge ( = 4.44, S.D. = 0.58).